2021
DOI: 10.1111/ijcp.14869
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chest CT scan findings with SOFA score, CRP, comorbidity, and mortality in ICU patients with COVID‐19

Abstract: Objective This study aimed to investigate the relationship between chest computed tomography (CT) scan findings with sequential organ failure assessment (SOFA) score, C‐reactive protein (CRP), comorbidity, and mortality in intensive care unit (ICU) patients with coronavirus disease 19 (COVID‐19). Method Adult patients (≥18 years old) with COVID‐19 who were consecutively admitted to the Imam‐Reza Hospital, Tabriz, East‐Azerbaijan Province, North‐West of Iran between Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
1
0
1
Order By: Relevance
“…[12] However, the relationship between other symptoms and mortality could not be demonstrated both in the same study and in the study of Martos Pérez et al [14] There was a significant correlation between the extent of lung involvement and mortality. In the study of Hejazi et al [15] on intensive care patients in Iran, they found that multilobar involvement was associated with comorbidity and poor prognosis, but they could not associate it with mortality. However, the study of Aydemir et al [16] was similar to ours, they found a relationship between multilobar involvement and the severity and mortality of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…[12] However, the relationship between other symptoms and mortality could not be demonstrated both in the same study and in the study of Martos Pérez et al [14] There was a significant correlation between the extent of lung involvement and mortality. In the study of Hejazi et al [15] on intensive care patients in Iran, they found that multilobar involvement was associated with comorbidity and poor prognosis, but they could not associate it with mortality. However, the study of Aydemir et al [16] was similar to ours, they found a relationship between multilobar involvement and the severity and mortality of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…La literatura está dividida al reportar la efectividad de SOFA para el Covid-19. Algunos estudios demuestran una correlación significativa entre la TC y el SOFA al ingreso, afirmando que el SOFA es una buena herramienta para predecir la gravedad y el desenlace de la enfermedad (21) . Un SOFA mayor o igual a 2 en el momento del ingreso hospitalario puede ser un predictor de la necesidad de ingreso en la UCI (22) y un SOFA elevado en las primeras 48 horas puede sugerir una alta tasa de mortalidad (7) .…”
Section: Discussionunclassified